Peran Sales Promotion dan Brand Equity dalam Memengaruhi Re-purchase Intention Produk Fashion di Marketplace - Yudhistira Rangga Paksi; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Indonesia's e-commerce growth in 2020 has increased quite a lot compared to 2019. Fashion is rising and safe to shop online at Indonesian e-commerce and Shopee as one of the largest E-commerce in Indonesia. Erigo, as a local Indonesian brand, competes with competitors to get customers repurchase intentions. The article examines the impact of sales promotion and brand equity on customer intention to repurchase Erigo local brand products by studying the Shopee marketplace. The sample of this research is respondents who have purchased Erigo products at Shopee. This primary data was collected by questionnaire and observation. Data analysis with multiple linear regression and sample used was 121 respondents. The sampling method used nonprobability sampling, and the sampling technique was judgmental sampling. The results showed that Sales Promotion and Brand Equity had a significant influence on the repurchase intention of Erigo products. This study recommends Erigo to maintain brand equity. Erigo also must keep their unique promotions, such as low prices at the end of the month and get free items for the purchase. Erigo can also use the findings for its brand evaluation.